Establishment and characterization of three canine ameloblastoma cell lines with genomic and transcriptomic profiles - Stephanie Goldschmidt; Natalia Vapniarsky; John D. McPherson; Iris Rivas; Christine Ly; Abraham Morales; Daniel York; Robert Rebhun; Maria Soltero-Rivera (PLoS ONE, 2026)
Establishment of canine acanthomatous ameloblastoma (CAA) cell lines has profound importance in pre-clinical in vitro testing. The goal of this study was to develop, authenticate, and characterize three CAA cell lines. Cell lines were developed with standard cell culture techniques from dogs with naturally occurring CAA. Each cell line was authenticated as canine with a validated PCR panel. Epithelial cell origin was confirmed with pan-CK flow cytometry. Next generation DNA and RNA sequencing characterized features of the cell lines and compared them to the parent tumor. We confirmed that all cell lines maintained mutations seen in the parent tumors including a missense HRAS mutation and RTK-RAS pathway upregulation across all samples. Other common mutations (2/3 cell lines and their parent tumors) included ADGRA3, DNAH7, F10, KIAA1671, OGFR, SLC6A17, SNX7, SPTBN5, TENM4 , and YEATS2 . We compared the transcriptional profiles from our parent tumors and established cell lines to historical transcriptomic analysis of CAA and healthy gingiva. We confirmed the same canonical CAA molecular features of primary tumors across studies with distinct clustering from healthy gingiva. Further, we documented that the cell lines maintained upregulated genes that are seen within in vivo CAA across both studies including upregulated GPC4 and ETV5 as well as gene sets associated with the presence of epithelial-mesenchymal transformation, KRAS, Pi3K-AKT signaling, and hedgehog signaling pathways. Thorough characterization of the mutational and transcriptional profiles of the established cell lines, especially in context to how they differ from the parent tumors, sets the platform for translational in vitro testing.